Vector Control of Zoonotic Arbovirus Disease in Indonesia - Fitrine Ekawasti; Eny Martindah (WARTAZOA, Indonesian Bulletin of Animal and Veterinary Sciences, 2016)
Zoonotic Arbovirus diseases which are caused by the genus of Flavivirus, Alphavirus, and Bunyavirus, are transmitted through potential vectors. These diseases are commonly occurred, especially in tropical countries, including Indonesia. They can affect the economic development because of the high morbidity and mortality. This paper describes the incidence of zoonotic Arbovirus in Indonesia and the strategy to control its vector. Factors that support the occurrence of zoonotic Arbovirus diseases are environmental, demographic and behavioral changes, as well as advanced technology, transportation and global trade. These diseases would not occur without the role of vectors. Vector control can be carried out effectively through longitudinal surveillance to identify types of potential vectors in the area. Therefore to prevent the increased incidence of the diseases, controlling the vector is necessary.